Weight loss for individuals with type 2 diabetes following a very‐low‐calorie diet in a community‐based setting with trained facilitators for 12 weeks. Issue 5 (23rd August 2013) - Rolland, C.; Lula, S.; Jenner, C.; Dyson, L.; Macdonald, I.; Johnston, K. L.; Broom, I.
Summary: What is already known about this subject: Approximately 80% of people with type 2 diabetes mellitus (T2DM) are overweight or obese. Weight loss produces numerous benefits in T2DM. People with T2DM have difficulty losing and maintaining weight. What this study adds: Provision of a very‐low‐calorie diet (VLCD) with group support and behaviour therapy for patients with T2DM is feasible within a community‐based setting with trained facilitators. VLCD approaches for weight management in T2DM can achieve more than 90% of weight loss as compared with obese individuals without T2DM. Identification of the need to investigate the full impact of this approach in patients with T2DM by assessing changes in glycaemia, liver function and medication. Approximately 80% of people with type 2 diabetes mellitus (T2DM) are overweight or obese, and obesity compounds the cardiovascular risk of T2DM. The aim of this retrospective study was twofold: first, to investigate whether a 12‐week community‐based very‐low‐calorie diet (VLCD) programme can result in important weight loss; and second, to investigate any potential difference in the weight loss achieved using this community‐based approach in individuals with and without T2DM. Three hundred and fifty‐five participants with T2DM were matched for age, body mass index (BMI) and gender to participants without T2DM (total cohort comprised 204 males: 506 females (mean ± standard deviation); age (years) 54.0 ± 9.1; BMI (kg m −2 ) 41.6 ± 8.1; weight (kg) 116.1 ± 25.1). The programme included a daily intake of 550 kcal in addition to group support and behaviour therapy provided by trained facilitators within a community‐based setting. After 12 weeks, there was significant weight loss within each group when compared with baseline (T2DM: 115.0 ± 24.4 kg vs. 96.7 ± 21.4 kg, P  < 0.0001; non‐T2DM: 117.2 ± 25.8 kg vs. 97.3 ± 22.2 kg, P  < 0.0001). At 12 weeks, weight change (−18.3 ± 7.3 kg vs. −19.9 ± 7.0 kg, P  = 0.012) and BMI change (−6.7 ± 2.9 kg m −2 vs. −7.1 ± 2.1 kg m −2, P  = 0.011) were significantly less in the T2DM group when compared with the non‐T2DM group. Our results suggest that the use of VLCD approaches for weight management in T2DM can achieve more than 90% of the weight loss seen in obese individuals without T2DM.